2007
DOI: 10.1002/gps.1773
|View full text |Cite
|
Sign up to set email alerts
|

Survival in the community of the very old depressed, discharged from medical inpatient care

Abstract: Depression is common in older people discharged from acute medical care and is a major risk factor for reduced duration of community survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Depression has been described in quantitative research as a mortality risk in older persons (Sutcliffe et al, 2007;Wilson et al, 2007). Sampson et al (2009) revealed that cognitive impairment and lack of social support are independent mortality risk factors for older depressed persons, while Greenlee et al (2010) demonstrated how anxiety impairs remission of depression during treatment of older persons.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been described in quantitative research as a mortality risk in older persons (Sutcliffe et al, 2007;Wilson et al, 2007). Sampson et al (2009) revealed that cognitive impairment and lack of social support are independent mortality risk factors for older depressed persons, while Greenlee et al (2010) demonstrated how anxiety impairs remission of depression during treatment of older persons.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of minor and subthreshold depression are also high in these geriatric populations and have been shown to be clinically significant in terms of significant in terms of persistence and negative effects on health and functioning. [59]…”
Section: Introductionmentioning
confidence: 99%
“…If the reason of these empirical peaks is only related to widowhood, this could possibly suggest that two waves of depression resulting from widowhood occur in the population at two different ages. For example, depressive people could die at younger ages, as already reported in some literature [42]. None of the scenarios included such a rule.…”
Section: Discussionmentioning
confidence: 84%